ENTREPRENEURIAL OPPORTUNITIES IN ORGANIC MARKETS: A COMPARATIVE STUDY OF CONSUMER PERCEPTION TOWARDS ORGANIC AND CONVENTIONAL PRODUCTS IN HYDERABAD - P Chakradhar; K Arjun Goud; Patcha Bhujanga Rao; M Vijaya Bhaskar Reddy, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The purpose of this research is to compare how city dwellers feel about organic and conventional goods. Although awareness and preferences among consumers for organic products have grown in recent years, conventional products are still for many people's first choice. People are becoming more health-conscious and paying more attention to what they eat, which influences the health of individuals and the environment. Health benefits, pricing, and environmental safety were the main points of this paper's analysis of what motivates consumers to make certain purchases. Information for the sample size comes from the standard questionnaire. Consumers' perceptions of the benefits and drawbacks of organic and conventional products are laid bare in the survey. This so-called study concluded that, when compared to conventionally grown food, organic products provided the better nutritional benefits to most respondents.